2014
DOI: 10.1002/acn3.136
|View full text |Cite
|
Sign up to set email alerts
|

Brain alterations within the first 100 days of HIV infection

Abstract: ObjectiveBrain involvement is a serious complication of HIV infection. The earliest changes in the brain, which represents an anatomic site for viral persistence, are largely unknown.MethodsThis investigation used quantitative Magnetic Resonance methodologies, including high resolution and diffusion tensor (DTI) imaging, to evaluate the brain in 15 HIV and 20 seronegative subjects. All HIV subjects were antibody nonreactive with assay-estimated infection duration of less than 100 days.ResultsBrain volumetric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
89
3
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 45 publications
7
89
3
3
Order By: Relevance
“…42 Often decreases in FA have been seen in HIV+ individuals compared to HIV- controls. 15,18,33,43-46 While we observed a decrease in FA for HIV+ individuals using DTI, DBSI revealed that observed changes in DTI may in fact reflect the continued presence of inflammation. Inflammation can appear as axonal loss from reduced diffusion along the primary direction yielding a concurrent reduction in FA.…”
Section: Discussionmentioning
confidence: 54%
“…42 Often decreases in FA have been seen in HIV+ individuals compared to HIV- controls. 15,18,33,43-46 While we observed a decrease in FA for HIV+ individuals using DTI, DBSI revealed that observed changes in DTI may in fact reflect the continued presence of inflammation. Inflammation can appear as axonal loss from reduced diffusion along the primary direction yielding a concurrent reduction in FA.…”
Section: Discussionmentioning
confidence: 54%
“…PC5 is rich in the cerebral cortex and dentate gyrus, while PACE4 is particularly abundant in the cerebellum. Notably, the frontal cortex and the hippocampus are major sites of motor and/or cognitive functions, which are selectively damaged in HAND (11). Although indicative of coexpression, this does not prove that the PAR1 and PC proteins are colocalized intracellularly.…”
Section: Figmentioning
confidence: 99%
“…HIV infects the central nervous system soon after primary infection (11) and establishes a tissue reservoir by productively infecting brain myeloid cells, which eventually leads to neurocognitive impairment in a subset of patients (reviewed in reference 12). HIV-associated neurocognitive disorder (HAND) represents a daunting and ongoing challenge in the diagnosis and care of people with HIV/AIDS.…”
mentioning
confidence: 99%
“…One prior study revealed reduced total cortical volume and enlarged third ventricle in PHI, though the study included HIV+ individuals receiving cART [6, 7]. Thus, the natural course of untreated HIV-dependent volume changes is not established, as early initiation of cART may preclude further neural injury.…”
Section: Introductionmentioning
confidence: 99%